Investigación musical. Experiencias del Congreso de Investigación Musical en Cali, 2015 (2016)
The interest and dissemination of the results of musical research in the country have shown a boom in the last two decades, partly because of the need to meet the minimum or high quality requirements that are required in university programs and partly because of the recognition to the diversification of the musical task, and the different looks towards the trade, that compromises so much learning processes, sequences of transmission, conservation of patrimony as new technologies in the creation, the interpretation, the production and the diffusion and in short the stay in a globalized world and communicated in multiple ways, which three or more decades ago made such actions less feasible.